PROFESIONALISME APARATUR PEMERINTAHAN DAERAH PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH DAN STATISTIK KABUPATEN NAGEKEO PERIODE 2009 DAN PERIODE 2013 - Hubertus Oja (Universitas Musamus, Merauke, Papua, 2014)
The professionalism of local governance reform is an important part in materializing good local governance. This study aims to analyse the professionalism of the state apparatus in the Regional Development Planning Board and Statistics (BAPPEDAS) of Nagekeo Regency in the period of 2009 to 2013.This quantitative comparative study was carried out at the Regional Development Planning Board and Statistics (BAPPEDAS) of Nagekeo Regency and the data were collected by means of questionnaire, interview, and documentary study. The sample was selected with saturated sampling technique. The data were analysed with statistical comparative analysis and presented in a description. The study reveals that the professionalism of the state apparatus in the Regional Development Planning Board and Statistics (BAPPEDAS) of Nagekeo Regency in qualitative view is in the medium category. The comparative rate shows that the apparatus’professionalism in 2009 was 48,90% and in 2013 was 54,61% with a difference of 5,71%. The fact of finding indicates that the apparatus’s professionalism in 2013 improved when compared to the one in 2009.This result proves that in quantitative speaking there is an increase of professionalism of the apparatus but in qualitative view there is no improvement because the range is still in the medium category.